Modeling of Strengthening Lecturers Creativity through Exploration of Positive and Dominant Influence Factors - Mahendrawan, Ersam; Hardhienata, Soewarto; Setyaningsih, Sri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
One of the challenges experienced by every university is to improve the quality of the tridharma of higher education, where the most important component in improving the quality is the lecturer. Pamulang University as one of the universities with the largest number of lecturers in Indonesia, namely 2024 lecturers, of course requires many aspects to improve its quality in order to realize the vision it wants to achieve. This study aims to produce a model of strengthening creativity in the form of a constellation model of the influence between variables and their mathematical model. From the mathematical model, it can be derived into a research hypothesis. The research begins by interviewing informants who are considered competent in providing the expected answers for further data reduction, data codification, data analysis, and conclusion drawing. The research was conducted at Pamulang University from June 2020 to February 2021. From the research that has been carried out, it is concluded that there are variables that are thought to have a positive and dominant influence on creativity, namely professional commitment, job satisfaction, and achievement motivation, while the intervening variables are job satisfaction and achievement motivation